2018
DOI: 10.15453/2168-6408.1393
|View full text |Cite
|
Sign up to set email alerts
|

Screens or MP4s: Acquiring Clinical Competencies Through the Use of e-OSPEs in Occupational Therapy

Abstract: The assessment of clinical competence of undergraduate students is a crucial part of higher education training in occupational therapy. The use of online objective standardized practical examinations (e-OSPEs) was piloted as a technological innovation to determine student learning needs. An action research framework with four phases was used. Descriptive statistics in the form of frequency tables and percentages were used to report survey results. The students had multiple practice opportunities before uploadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is a necessary skill our students need to develop during their training for effective practice in a fluid and changing health care context. Local research by colleagues in occupational therapy has reported that e-assessment (video submissions) can contribute to clinical skills acquisition (Cloete, Jacobs-Nzuzi Khuabi & Van Niekerk 2018). They implemented the e-OSPE following a reduction in their divisional budget.…”
Section: Video Portfoliomentioning
confidence: 99%
“…This is a necessary skill our students need to develop during their training for effective practice in a fluid and changing health care context. Local research by colleagues in occupational therapy has reported that e-assessment (video submissions) can contribute to clinical skills acquisition (Cloete, Jacobs-Nzuzi Khuabi & Van Niekerk 2018). They implemented the e-OSPE following a reduction in their divisional budget.…”
Section: Video Portfoliomentioning
confidence: 99%
“…This is a necessary skill our students need to develop during their training for effective practice in a fluid and changing health care context. Local research by colleagues in occupational therapy has reported that e-assessment (video submissions) can contribute to clinical skills acquisition (Cloete, Jacobs-Nzuzi Khuabi & Van Niekerk 2018). They implemented the e-OSPE following a reduction in their divisional budget.…”
Section: Video Portfoliomentioning
confidence: 99%
“…This is a necessary skill our students need to develop during their training for effective practice in a fluid and changing health care context. Local research by colleagues in occupational therapy has reported that e-assessment (video submissions) can contribute to clinical skills acquisition (Cloete, Jacobs-Nzuzi Khuabi & Van Niekerk 2018). They implemented the e-OSPE following a reduction in their divisional budget.…”
Section: Video Portfoliomentioning
confidence: 99%